Epidemiology of gallbladder cancer - Rawla, Prashanth; Sunkara, Tagore; Thandra, Krishna Chaitanya; Barsouk, Adam (Clinical and Experimental Hepatology, 2019)
According to GLOBOCAN 2018 data, gallbladder cancer (GBC) accounts for 1.2% of all global cancer diagnoses, but 1.7% of all cancer deaths. Only 1 in 5 GBC cases in the United States is diagnosed at an early stage, and median survival for advanced stage cancer is no more than about a year. The incidence of the disease is increasing in the developed world. Gallstones, biliary cysts, carcinogen exposure, typhoid, and Helicobacter pylori infection, and abnormal pancreaticobiliary duct junctions are all risk factors, many of which account for its geographical, ethnic and sex distribution. Genetics also plays a strong role, as about a quarter of GBC cases are considered familial, and certain ethnicities, such as Native Americans, are at far higher risk for the neoplasm. Prevention includes weight loss, vaccination against and treatment of bacterial infections, early detection and elimination of polyps and cysts, and avoidance of oral estrogen replacement therapy.